KEPUASAN KERJA, KOMITMEN ORGANISASI DAN TURNOVER INTENTION DI PT. HILLCONJAYA SAKTI, CAKUNG, JAKARTA TIMUR - Anggraeni, Mia; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2016)
This study aims to analyze the effects of job satisfaction and organizational commitment to ward employees turnover intention in PT. Hillconjaya Sakti, Cakung, East Jakarta. This study utilized data analysis method by using SmartPLS software. The sample used in this study are 98 respondents. Data was collected by questionnaires, surveys, interviews, and literature review. The results reveals that: 1) job satisfactions significantly and negatively affect on the organizational commitment, 2) the organizational commitment significantly and negatively affects onÂ  thr turnover intention, 3) job satisfactions significantly and negatively affect on the turnover intention. Implications for managerial practice were discussed